2007
DOI: 10.2190/a407-22rr-50x6-2830
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Sources of Teachers' Instructional Technology Use Through the Decomposed Theory of Planned Behavior

Abstract: Based on the decomposed theory of planned behavior, this study used path analysis to examine the relative strength of the factors that influence teachers' use of instructional technology. The study focused on teachers' use of word processors, spreadsheets, presentation software, e-mail, and Web browsers. A path analysis was performed on self-reported data from 242 secondary science teachers in Taiwan. Results showed that the decomposed theory of planned behavior seriously over simplified the web of forces that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 25 publications
4
38
1
6
Order By: Relevance
“…Paraskeva, Bouta, & Papagianni (2008) found that it was a combination of self efficacy, with a positive attitude, and a desire to use technology in their teaching, that was the greatest indicator of whether teachers would actually use technology or not. Our study builds on this previous literature (Lee, Cerreto, & Lee, 2010;Palak & Walls, 2009;Sadaf, Newby, & Ertmer, 2011;Shiue, 2007) in that the findings are consistent in terms of the separate variables, but our findings extend the prior knowledge in that we included self-determination theory.…”
Section: Discussionsupporting
confidence: 82%
“…Paraskeva, Bouta, & Papagianni (2008) found that it was a combination of self efficacy, with a positive attitude, and a desire to use technology in their teaching, that was the greatest indicator of whether teachers would actually use technology or not. Our study builds on this previous literature (Lee, Cerreto, & Lee, 2010;Palak & Walls, 2009;Sadaf, Newby, & Ertmer, 2011;Shiue, 2007) in that the findings are consistent in terms of the separate variables, but our findings extend the prior knowledge in that we included self-determination theory.…”
Section: Discussionsupporting
confidence: 82%
“…Il s'agit, entre autres, de l'autoefficacité générale de l'enseignant (Paraskeva, Bouta et Papagianni, 2008), de sa facilité à utiliser les TIC (Shiue, 2007), du contrôle perçu envers les TIC (Shiue, 2007) et de son intention de les intégrer dans son enseignement (Shiue, 2007;Van Acker, Van Buuren, Kreijns et Vermeulen, 2011). D'autres facteurs d'influence ressortent dans les écrits, notamment le fait de détenir des connaissances et des aptitudes liées aux TIC (Kreijns, Van Acker, Vermeulen et Van Buuren, 2013;Van Acker et al, 2011), l'attitude à l'égard de ces outils, la perception d'avantages à les intégrer dans sa pratique pédagogique et les états physiques, dont le sentiment d'anxiété (Van Acker et al, 2011).…”
Section: Compétence Professionnelle Relative Aux Ticunclassified
“…Même si plusieurs des études recensées s'intéressent à l'autoefficacité comme facteur d'influence de l'intégration des TIC dans un contexte scolaire (voir Bursal et Yigit, 2012;Grenon, 2007;Kreijns et al, 2013;Liang et Tsai, 2008;Pamuk et 2009; Paraskeva et al, 2008;Robertson et Al-Zahrani, 2012;Sang et al, 2010;Shiue, 2007;Van Acker et al, 2011;Van Dinther et al, 2011), peu ont étudié de façon systé-matique les sources d'autoefficacité (Gloudemans, Schalk, Reynaert et Braeken, 2013 Zeldin et Pajares, 2000), de même que des états physiques et émotionnels (Hodges et Murphy, 2009;Van Acker et al, 2011). À la lumière de ces résultats, il est possible de constater l'absence de consensus concernant l'importance de chacune des sources d'autoefficacité.…”
Section: Compétence Professionnelle Relative Aux Ticunclassified
See 2 more Smart Citations